ATOMIC FORCE MICROSCOPY STUDIES FOR ANTIBACTERIAL ACTIVITY OF GARCINIA XANTHOCHYMUS SEED EXTRACTS - SHIVANAND PAYAMALLE,; HOSAKATTE NIRANJANA MURTHY, (International Journal of Pharma and Bio Sciences, 2016)
The aim of present study was the evaluation of antibacterial activity of G. xanthochymus seed extracts against some pathogenic bacteria like Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa and Escherichia coli and to analyze the mechanism of its antibacterial action by Atomic force microscopy (AFM). The minimum inhibitory concentrations varied from 12.5 to 50.0 µg/ml. The AFM study reveals that S. aureus strain treated with petroleum ether extract showed a reduction in the cell size, formation of maximum cell clusters indicating the maximum damage to the cells whereas cell rupture and surface roughness was observed in B. cereus and E. coli strains treated with petroleum ether extract. The petroleum ether seed extract was responsible for the highest antibacterial activity against these strains. None of the seed extracts showed any activity against P. aeruginosa.